PERANCANGAN POLIMER KOMPOSIT DENGAN SERAT TEBU DAN FIBER GLASS UNTUK PENINGKATAN KEKUATAN TERHADAP UJI TARIK: PERANCANGAN POLIMER KOMPOSIT DENGAN SERAT TEBU DAN FIBER GLASS UNTUK PENINGKATAN KEKUATAN TERHADAP UJI TARIK - Sutrisno . (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2025)
This study investigates the effect of varying weight fractions of sugarcane fiber and fiberglass on the mechanical properties of polyester resin-based composite, with a focus on improving tensile strength. Sugarcane fiber, a lignocellulosic natural reinforcement with a length of 3 cm, was used alongside fiberglass as a synthetic reinforcement to evaluate the performance of hybrid composites. Specimens were fabricated using the hand lay-up method with five combinations of sugarcane fiber (0–10%) and fiberglass (0–10%), while the polymer resin and catalyst comprised 90% of the total composite weight. Tensile testing was conducted according to ASTM D638-01 using a Universal Testing Machine. The evaluated parameters include maximum tensile stress, strain, and elastic modulus. Experimental results showed the highest tensile strength of 88,186 MPa at 0% sugarcane fiber and 10% fiberglass, and the lowest value of 27,154 MPa at 10% sugarcane fiber with no fiberglass. The maximum strain observed was 0.0050 mm/mm, and the minimum was 0.0012 mm/mm. The highest elastic modulus was 71,287 MPa, while the lowest was 5,384 MPa. These results confirm that an optimal combination of natural and synthetic fibers significantly enhances the mechanical performance of the composite. This research highlights the potential of sugarcane fiber as a sustainable reinforcement alternative in the development of environmentally friendly composite materials.